Pupuk Organik sebagai Subtitusi Pupuk Anorganik Menuju Pertanian Lada Perdu Organik - Dibyo Pranowo; Syafaruddin Syafaruddin (Jurnal Tanaman Industri dan Penyegar, 2011)
Utilization of organic fertilizer as a substitute of anorganic fertilizer toward organic pepper shurbs have been done at experimental garden Pakuwon by using pot system in paranet screen house in May-December 2009. The experimental design of the study  is Group Randomized Factorial Design, The first factor consists of two types of pepper hybrid LH4-5-5 (V1) and LH 6-2 (V2), and use Petaling 1 (V3) as a comparison. The second factor is the technology package, is doses of organic fertilizers as a substitute for anorganic fertilizers with composition level of media: P0 = soil 1:1 organic fertilizer + 100%  anorganic fertilizer recommendation (GAP), P1 = soil 1: 2  organic fertilizer + 80% anorganic fertilizer GAP, P2 = soil 1: 3  organic fertilizer + 60%anorganic fertilizer  GAP, P3 = soil  1:4  organic fertilizer  + 40% anorganic fertilizer GAP and P4 = soil 1: 5 20% organic fertilizer+ anorganic fertilizer GAP. The number of plants per treatment is 5 plants and 3 replication, so therefore total number is 225 plants. The observed parameters : plant height, number of primary and secondary branches, stem base diameter, node length and leaves number per branch, also macro and micro nutrient analysis of each of media treatment. The result showed that anorganic fertilizer NPK-Mg requirement on pepper shrubs at vegetative stage can be substituted with 80% organic fertilizer and 20% anorganic fertilizer.  Hybrid pepper LH 6-2 and LH 4-5-5 higher potencial production than Petaling 1. At 4 month after planting did not  show no significant differences of vegetative growth between treatment and variety, this result shown probability of pepper shrubs cultivation on pot system can be cultivated with organic system.